The power of a patient's story: a practice in cultural humility - Schmidt, Randall B. (Frontiers in Global Women's Health, 2025)
As the United States grows increasingly diverse, healthcare providers will encounter changing patient populations. In obstetrics, patients often come with personal delivery priorities shaped by different life experiences, cultural expectations and personal perspectives, which may differ from those of their provider. Invariably, cultural conflicts can occur, especially when patient and provider priorities do not align. This article shares the story of a Congolese refugee mother within an urban metro area who faced such conflict when delivery preferences could not be accommodated. Highlighting communal apprehension to Cesarean delivery within the Congolese community, this piece also emphasizes how obstetrics providers can improve care for culturally diverse patients. In addition, this piece also discusses an American College of Obstetricians and Gynecologists (ACOG) committee opinion, cultural humility and its incorporation into future curriculum for medical education, and the author's personal reflection of this story's impact.